Optimizing Learning Quality: Overcoming Learning Challenges in Children through the Implementation of Scramble Learning Model Assisted by Educandy - Jasid, Adhara; Afnita, Afnita (JURNAL AL-TANZIM, 2024)
The main focus of this research is applying the Scramble learning model assisted by Educandy media as an interactive approach to overcome student difficulties so that the quality of learning can improve. The research method used was an experiment using score data from a test of understanding archaic words. The population of this research is all class X students of SMA Negeri 1 Keritang for the 2023/2024 academic year, with a total of 259 students. The research results show an influence of the scramble learning model assisted by Educandy media on understanding archaic words. This is proven by obtaining the price value tcount > ttable with df = 63 and α = 0.05, namely 1.673 > 1.669, meaning that H0 is rejected. Thus, it can be proven that the scramble learning model assisted by Educandy media influences the understanding of archaic words in the saga texts of class X SMA Negeri 1 Keritang students. This research implies that using the Scramble learning model assisted by Educandy media is an effective alternative learning method in Islamic education. Islamic education management can consider integrating technology and interactive approaches such as those proposed in this research as strategies to improve the quality of learning in educational institutions.